2005
DOI: 10.1177/0018726705058502
|View full text |Cite
|
Sign up to set email alerts
|

Living with enterprise in an enterprise economy: Freelance and contract workers in the media

Abstract: Changes in organizational structures, logics and employment practices in the media industries – critically the outsourcing of labour, whereby employees become freelance workers – supply an ideal context in which to explore the extent to which, and the ways in which, ideological and structural pressures encourage workers to accept the logic and imperatives of enterprise. An important and influential body of literature identifies the ‘enterprising self ’ as a central paradigmatic concept underpinning the rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
212
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(222 citation statements)
references
References 8 publications
3
212
0
6
Order By: Relevance
“…Here, the figure of the 'entrepreneur' came to symbolize the new, ideal public servant who approached work from a private sector mindset that prioritizes profit and innovation (Du Gay, 1996), implicitly distracting from an emphasis on service and vocation. Among contract workers and others in precarious employment, the dominance of such a discourse posits an entrepreneurial ideal as the best way for workers to view their situations (Parker, 2007;Storey, Salaman and Platman, 2005). This can lead to a sense of failure when the individual struggles to live up to the ideal in economically uncertain times (Tretheway, 2001).…”
Section: The Signifier Entrepreneurmentioning
confidence: 99%
“…Here, the figure of the 'entrepreneur' came to symbolize the new, ideal public servant who approached work from a private sector mindset that prioritizes profit and innovation (Du Gay, 1996), implicitly distracting from an emphasis on service and vocation. Among contract workers and others in precarious employment, the dominance of such a discourse posits an entrepreneurial ideal as the best way for workers to view their situations (Parker, 2007;Storey, Salaman and Platman, 2005). This can lead to a sense of failure when the individual struggles to live up to the ideal in economically uncertain times (Tretheway, 2001).…”
Section: The Signifier Entrepreneurmentioning
confidence: 99%
“…In short, it allows the worker to reframe their labour through a rationalized set of intentions, thereby replacing determinative pressures from the social context for an agential view of the self. That this tendency is not limited to musicians but is more widely the case for other freelancers is borne out by Storey et al (2005), where we can see that an ethos of enterprise is a strong normative imperative for freelancers, and moreover more widely reflected in what Du Gay (1996) has called 'enterprise culture'. Driven by a desire to be entrepreneurial, the media freelancers studied by Storey et al (2005) reproduced the discourse of enterprise even through their shortcomings; for example, by blaming the inability to obtain work on market failure rather than a hiatus in their skillset.…”
Section: Discussionmentioning
confidence: 99%
“…This ambiguity leads to a shakiness and vulnerability that makes it difficult for contract workers to establish their credibility and to secure their identity. In studies of freelance media workers, Storey et al (2005) found much of their knowledge tied up with both disciplining and judging their identities while protecting these identities in experiences of rejection, loss of income and loss of mastery. Clearly, the 'knowledge' of contracted workers such as the women featured in this article is definitionally heterogeneous and difficult to categorise.…”
Section: Boundaryless Contract Workmentioning
confidence: 99%
“…Alvesson 2001;Storey et al 2005) that proving the 'knowledge' of contract knowledge work is mostly about managing identity and impression.…”
Section: Proving Knowledge In a Market Of Impressionsmentioning
confidence: 99%